The Difference of the English Teaching and Learning Process of SMA in Urban and Rural Areas in Yogyakarta - Eka Ariestina (PBI 16 UMY 001, 2016)
*1 The success of the learning process is influenced by several factors such as teachers, learners, infrastructure, environment and teaching learning strategy. This research aims to know the factors influencing in the differencess of teaching and learning process in urban and rural areas. The research used a qualitative design using in-depth interview as the instrument. The participants of the research were two English teachers, one was from an urban school and another one was from a rural school. The findings showed that in terms of teacher competence the urban teacher emphasized two competencies, namely professional competence and pedagogical competence, while the teacher in rural area emphasized on pedagogical competence as a reference in teaching. In terms of learners, the teacher in urban stated that most students came from midle to high income families, while in rural area; the students came from low income families. In terms of the English ability, the students in urban area not only gain knowledge of English from school, but also from external factors. In rural area the students get the knowledge of the English language only from their school. Related to the infrastructure, the school in urban area is more complete than the infrastructure of the school in rural area. In term of school environment, school environment in urban area was less convenient because it was near the noisy high way. Meanwhile, the school environment in rural area is very comfortable because it is located in quiet area. The last finding was about teaching and learning strategy. The teacher in urban area used more strategies, while the teacher in rural area used e-book as a reference for teaching and implementing school activities. Related to the classroom management, both teachers in urban and rural areas implemented group discussions in their classes.